Pendragon. Book seven, The Quillan games [compact disc, unabridged] - MacHale, D. J. (MacHale, D. J. Pendragon, 2006)
Quillan is a territory on the verge of destruction. The people have lost control of their own future and must struggle simply to survive. The only chance they have of finding a better life is by playing the Quillan Games. Hosted by a strange pair of game masters, Veego and LaBerge, the games are a mix of sport and combat.